2017
DOI: 10.1103/revmodphys.89.011001
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium: Persistent spin textures in semiconductor nanostructures

Abstract: Device concepts in semiconductor spintronics make long spin lifetimes desirable, and the requirements put on spin control by schemes of quantum information processing are even more demanding. Unfortunately, due to spin-orbit coupling electron spins in semiconductors are generically subject to rather fast decoherence. In two-dimensional quantum wells made of zinc-blende semiconductors, however, the spin-orbit interaction can be engineered in such a way that persistent spin structures with extraordinarily long s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
121
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 182 publications
5
121
1
Order By: Relevance
“…The study of a relativistic interaction, i.e., the spin-orbit coupling (SOC), has been one of the central themes in the context of spintronics, branch of electronics aiming at utilizing the electron's spin degree of freedom for device applications. 1 Many intriguing SOC-related phenomena were observed, such as spin relaxation 2,3 , optical spin orientation 4 , spin Hall effects [5][6][7][8] , persistent spin structures [9][10][11] , hidden spin polarization in centrosymmetric systems 12 , and the spin galvanic effects 13,14 . In particular, Dresselhaus 15 and Rashba [16][17][18] demonstrated that SOC splits spin-up and spin-down bands in nonmagnetic systems lacking inversion symmetry, inducing an effective magnetic field that depends on the crystal momentum k. Although the Dresselhaus and Rashba effects lead to different spin polarizations of the energy bands, they result in a similar band dispersion: the original spin degenerate bands split so that spin-up and spin-down bands shift towards opposite directions in k space, as shown in Fig.…”
mentioning
confidence: 99%
“…The study of a relativistic interaction, i.e., the spin-orbit coupling (SOC), has been one of the central themes in the context of spintronics, branch of electronics aiming at utilizing the electron's spin degree of freedom for device applications. 1 Many intriguing SOC-related phenomena were observed, such as spin relaxation 2,3 , optical spin orientation 4 , spin Hall effects [5][6][7][8] , persistent spin structures [9][10][11] , hidden spin polarization in centrosymmetric systems 12 , and the spin galvanic effects 13,14 . In particular, Dresselhaus 15 and Rashba [16][17][18] demonstrated that SOC splits spin-up and spin-down bands in nonmagnetic systems lacking inversion symmetry, inducing an effective magnetic field that depends on the crystal momentum k. Although the Dresselhaus and Rashba effects lead to different spin polarizations of the energy bands, they result in a similar band dispersion: the original spin degenerate bands split so that spin-up and spin-down bands shift towards opposite directions in k space, as shown in Fig.…”
mentioning
confidence: 99%
“…By fitting the experimental data with an appropriate theoretical model, it is possible to extract SOC strengths as well as dephasing, scattering, and, most prominently, spin relaxation rates [9][10][11][12][13][14][15][16][17][18]. Notably, a crossover from WAL to WL can even indicate spin-preserving symmetries [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…23, [36][37][38][39][40][41][42][43] Lead-and tin-based HOP possess a natural talent for Rashba and Dresslhaus couplings with a large SOC induced by Pb 2+ and Sn 2+ ions and a diverse zoology of crystal structures, including many deprived of centrosymmetry. It should be pointed out, that all the reported structures for lead, Page 5 of 29 5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A c c e p t e d m a n u s c r i p t tin or germanium halide perovskites are non-magnetic leading to a time-reversal symmetry of the electronic band structure.…”
mentioning
confidence: 99%